Reflection on the Role of Constitutional Court in Resolving 2004 General Election Dispute - Sri Hastuti Puspitasari (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The amendment of UUD 1945 implicates on the establishment of Constitutional Court. One of the authorities of the institution whose authority is equal to Supreme Court is to resolve the dispute of general election. The success of Constitutional Court in resolving the 2004 general election dispute proved that the principles of court justice have been implemented in order to keep democracy and to establish the constitution.Keywords: the role of constitutional Court, Election Dispute Resolution